Leadership, Innovation, and Profitability as Key Strategies to Enhance Digital Marketing: The Real Estate Sector in Ecuador - Iza Ortega, Kevin Orlando; Arias Benavides, Kassery Nicole; Viteri Escobar, Carlos Joel; Guerrero Carrasco, Martha Jaroslava; Sarmiento Chugcho, Carlos Bolívar (Espergesia, 2025)
This study employed a mixed-methods sequential explanatory design. Quantitative data were collected through surveys (n = 45), while qualitative data were obtained via semi-structured interviews, analyzed through inferential statistics and inductive content analysis. Quantitative findings revealed significant associations between leadership and profitability (ρ = .35, p = .019), as well as between digital marketing and economic performance (rs = .45, p = .002). Leadership demonstrated consistent effects in quantile regression, with β = 1.00 (p < .001) at the 25th quantile and β = 0.667 (p < .05) at the 50th quantile. In contrast, technological innovation did not show statistical significance (β = –0.03, p = .581), although its effect was marginal in the lower ranges of profitability. From the qualitative perspective, participants described a context of digital transition, where inspirational leadership fosters the use of platforms. The study concludes that limitations in training and automation remain.